Substrate specificity of haloalkane dehalogenases - Koudelakova, Tana; Chovancova, Eva; Brezovsky, Jan; Monincova, Marta; Fortova, Andrea; Jarkovsky, Jiri; Damborsky, Jiri (Biochemical journal (London. 1984), 2011)
An enzyme's substrate specificity is one of its most important characteristics. The quantitative comparison of broad-specificity enzymes requires the selection of a homogenous set of substrates for experimental testing, determination of substrate-specificity data and analysis using multivariate statistics. We describe a systematic analysis of the substrate specificities of nine wild-type and four engineered haloalkane dehalogenases. The enzymes were characterized experimentally using a set of 30 substrates selected using statistical experimental design from a set of nearly 200 halogenated compounds. Analysis of the activity data showed that the most universally useful substrates in the assessment of haloalkane dehalogenase activity are 1-bromobutane, 1-iodopropane, 1-iodobutane, 1,2-dibromoethane and 4-bromobutanenitrile. Functional relationships among the enzymes were explored using principal component analysis. Analysis of the untransformed specific activity data revealed that the overall activity of wild-type haloalkane dehalogenases decreases in the following order: LinB~DbjA>DhlA~DhaA~DbeA~DmbA>DatA~DmbC~DrbA. After transforming the data, we were able to classify haloalkane dehalogenases into four SSGs (substrate-specificity groups). These functional groups are clearly distinct from the evolutionary subfamilies, suggesting that phylogenetic analysis cannot be used to predict the substrate specificity of individual haloalkane dehalogenases. Structural and functional comparisons of wild-type and mutant enzymes revealed that the architecture of the active site and the main access tunnel significantly influences the substrate specificity of these enzymes, but is not its only determinant. The identification of other structural determinants of the substrate specificity remains a challenge for further research on haloalkane dehalogenases.
Keywords: Bradyrhizobium; aktivace enzymů; biologické modely; Agrobacterium tumefaciens; Escherichia coli; Enzyme Activation; Substrate Specificity; Models, Biological; Phylogeny; Mutant Proteins; Mycobacterium smegmatis; Mycobacterium bovis; Hydrolases; Sphingobacterium; mutantní proteiny; Rhodococcus; hydrolasy; substrátová specifita; fylogeneze; Xanthobacter